Analisis Dampak Penerapan Sistem Informasi Manajemen Terhadap Kinerja Organisasi Di Era Digital - Solekha, Nadira; Khairi, Rifqil; Mairiza, Diany (Journal of Economic, Management, Business, Accounting Sustainability, 2025)
This study aims to analyze the impact of implementing Management Information Systems (MIS) on organizational performance in the digital era. The main focus is to explore how MIS can enhance operational efficiency, decision-making processes, and the quality of organizational services. This research employs a literature review method by examining various sources and references related to MIS implementation across different types of organizations. The analysis process involves comparing previous studies, relevant information systems theories, and applicable case studies. This approach seeks to provide a comprehensive overview of the impact of MIS implementation on organizational performance. The findings indicate that MIS implementation significantly improves operational efficiency, accelerates decision-making, and enhances customer service. However, MIS implementation also poses challenges, such as high implementation costs and dependence on technology, which can be risky if not properly managed. Therefore, the success of MIS implementation largely depends on management commitment, human resource readiness, and appropriate technology selection.